The Effect of Eco Enzyme from Pineapple (Ananas comosus) Peel Waste on Soil pH, P Availability, Growth and Yield of Shallots (Allium cepa) in Ultisols - Tampubolon, Nadya Angelina; Muktamar, Zainal; Barchia, M. Faiz (BPFP Universitas Bengkulu, 2023)
Ultisols have a main problem of high soil acidity, low organic matter, low macronutrients, and very low P availability which can affect plant growth and yield. This research aims to determine the dynamics of soil pH, and P availability and determine the concentration of pineapple peel-based eco enzyme that produces the highest shallots. This research was carried out using a Completely Randomized Design (CRD) with treatment concentrations of eco enzyme 20% (200 mL eco enzyme and 800 mL water), 40% (400 mL eco enzyme and 600 mL water), 60% (600 mL eco enzyme and 400 mL water), 80% (800 mL eco enzyme and 200 mL water), 100% (100% eco enzyme), without treatment/control, and NPK fertilizer treatment. The results showed that the application of eco enzyme at a concentration of 60% was a sufficient concentration to improve soil characteristics and shallot yield as indicated by soil pH of 6.58, soil P of 6.75 ppm, number of bulbs 3.21 and weight of bulbs 4.69 g, as well as the application of 100% eco enzyme to provide soil organic C amounted to 3.76% which was higher than other treatments.